Research Productivity among Plastic Surgeons in the State of Israel: h-index and M-quotient Assessment. Issue 11 (4th November 2021) - Har-Shai, Lior; Ofek, Sar-El; Lavi, Idit; Cohen, Keren H.; Cohen, Avi A.; Ad-El, Dean D.; Shay, Tamir
Abstract : Background: The h -index has been proven in the US and Canada to be a solid tool to assess the quality and impact of individual scientific work in the field of plastic surgery. M-quotient is an additional metric that mitigates the h -index's inherent bias toward more seasoned researchers. The objective of this study was evaluating the relationship between h -index and M-quotient and research productivity among plastic surgeons in the state of Israel. Methods: A list of all Israeli board-certified plastic surgeons registered in the Israeli Society of Plastic and Aesthetic Surgery was obtained from the organization's website. Relevant demographic and academic factors of each surgeon were retrieved. The Scopus database was queried to determine each surgeon's h -index and M-quotient, among other bibliometric parameters. Results: Our study included 173 plastic surgeons, 90% of whom were men. In total, 49.7% were working in academically affiliated hospitals; 14.4% of the surgeons had an academic rank. The mean h -index was 6.13; mean M-quotient was 0.27. Statistical analysis demonstrated a positive correlation between total number of publications ( P < 0.0001), total number of citations ( P < 0.0001), the surgeon's seniority ( P < 0.0001), academic rank ( P = 0.007), appointed as past/present plastic surgery department director ( P < 0.0001), and working in an academic affiliated hospital ( P < 0.025). The same parameters were found to have a positive correlation with M-quotient. Conclusions: The h -index is an effective measure to compare plastic surgeons' research productivity in Israel. M-quotient is an ancillary tool for the assessment of research productivity among plastic surgeons, with the advent of neutralizing the surgeon's seniority.